Influence of board and shariah committee characteristic on takaful financial performance: a systematic literature review / Muhammad Adam Zainudin ... [et al.] - Zainudin, Muhammad Adam; Megat Mohamed Kamal, Megat Mohamed Shahrukh Akmal; Yusnizam, Muhammad Nizam Haziq; Abdul Rahim, Memiyanty (Universiti Teknologi MARA, 2021)
The board of directors and shariah committee characteristics play a vital role in ensuring the effectiveness of takaful firms in term of financial performance. This paper aims to provide a systematic review of characteristics related to board and shariah committee members that can enhance the financial performance of Tafakul firms. In addition, the paper also identifies the various measurement tools used by prior studies in measuring financial performance. This paper adopted Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and utilised two main journal databases: Scopus and Web of Science, to identify and select the articles to be analysed. Six articles have been identified and analysed systematically. As a result, the review was able to develop two main themes that are the board of directors and the shariah committee. Then, the examination of both themes contributed to the key characteristics, namely, size, non-executive directors, separation of Chairman and CEO role and Muslim member. The paper summarises the critical characteristics that significantly influence Tafakul firms' performance and describes that the empirical evidence does not provide a clear direction of the relationship. The unclear results might be due to the different cultures of the studies being conducted and included in this review. Furthermore, the method/tool used to measure Tafakul firm's financial performance in the selected articles is also different and unstandardised. As consequences, mixed and unclear results of the relationship between the characteristics of the board and shariah committee with financial performance are produced. Thus this offers some practical implications and lines for further research.